2005
DOI: 10.1139/b05-110
|View full text |Cite
|
Sign up to set email alerts
|

Revisions toPenicilliumser.Corymbifera: agents responsible for blue mould storage rot of various flower and vegetable bulbs

Abstract: Fifteen strains representing each Penicillium ser. Corymbifera taxa were compared using phenotypic and chemotaxonomic characters by cluster analysis and discriminant partial least squares regression. Variability in phenotypic expression of species strains resulted in a more fragmented classification compared with secondary metabolite expression. Although the observed phenotypic expression varied for strains cultured upon the same media, it was possible to classify strains into species groupings based only upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
(35 reference statements)
0
11
0
1
Order By: Relevance
“…Extensive collections of Penicillium species of the section Viridicata, many formerly placed in series Corymbifera (essentially segregates of P. corymbiferum Westling, syn. = P. hirsutum Dierckx) and primarily from Europe, have been extensively researched by Overy et al (2005aOvery et al ( , 2005bOvery et al ( , 2005c. A collection of lesser depth but exclusively from the United States and concentrated in the Pacific Northwest (PNW) has been similarly addressed (Dugan et al, 2011(Dugan et al, , 2014) with a detailed synopsis of taxonomy and nomenclature (Dugan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive collections of Penicillium species of the section Viridicata, many formerly placed in series Corymbifera (essentially segregates of P. corymbiferum Westling, syn. = P. hirsutum Dierckx) and primarily from Europe, have been extensively researched by Overy et al (2005aOvery et al ( , 2005bOvery et al ( , 2005c. A collection of lesser depth but exclusively from the United States and concentrated in the Pacific Northwest (PNW) has been similarly addressed (Dugan et al, 2011(Dugan et al, , 2014) with a detailed synopsis of taxonomy and nomenclature (Dugan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Komagata et al, 1996Tachibana et al, 2008 Penicillium stoloniferum Alsberg andBlack, 1913;Clutterbuck et al, 1932Ciegler et al, 1972Lindenfelser and Ciegler, 1977 Overy and Frisvad, 2003;Overy et al, 2005; Penicillium vanderhammenii Houbraken et al, 2011 Penicillium verrucosum Gedek et al, 1981;Moslem, 2013;Oh et al, 1998Penicillium viridicatum Bresler et al, 1995Ciegler et al, 1972Ciegler et al, , 1973Jiménez et al, 1991;Lund and Frisvad, 1994;Mintzlaff et al, 1972;Northolt et al, 1979;Oh et al, 1998 Trichoderma spp. 2 Lebed et al, 1978 …”
Section: Penicillium Rolfsiimentioning
confidence: 99%
“…Terrestric acid is rather closely related to penicillic acid, and is produced by P. aurantiogriseum, Penicillium crustosum (= Penicillium terrestre), Penicillium hirsutum, Penicillium hordei, Penicillium radicicola, Penicillium tricolor, Penicillium tulipae, Penicillium venetum and Magnaporte grisea = Pyricularia oryzae (Birkinshaw and Raistrick, 1936;Frisvad et al, 1994Lund and Frisvad, 1994;Overy and Frisvad, 2003;Overy et al, 2005;Sonjak et al, 2005;Yu et al, 2010). Production of terrestric acid by Penicillium griseoroseum (Da Silva et al, 2013), and Penicillium viridicatum (Birkinshaw and Samant, 1960) could not be confirmed , other metabolites produced by these organisms indicate they were in fact P. crustosum .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations